Beyond words : the European court of Justice and legal certainty in multilingual EU law - Paunio, Elina (University of Helsinki, Faculty of Law, 2011)
Abstract.
Keywords: lakikieli; kääntäminen; EU-oikeus; Euroopan unionin tuomioistuin; oikeusvarmuus; oikeuskulttuuri